Pengaruh Terapi Kelompok Terapeutik dan Pendidikan Kesehatan Terhadap Kecemasan Menghadapi Menarche pada Siswi Di Kelurahan Delima Kecamatan Tampan Pekanbaru - Usraleli Usraleli; Magdalena Magdalena (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Puberty is influenced by heredity, nation, environment, race or ethnicity, climatic factors, way of life, exposure to adult mass media and the environment. Children who have entered puberty will experience menarche. Menarche is an early sign of changes in the body such as breast growth, pubic and axillary hair growth, and fat distribution in the hip area. The symptom that often accompanies menarche is discomfort caused by the reduced volume of water in the body during menstruation. Other symptoms that are felt are headaches, aches in the legs and waist for several hours, stomach cramps and abdominal pain. Physical changes at puberty occur in tandem with emotional upheaval and adolescent psychological growth. Adolescent girls who will experience puberty show early signs of menarche showing feelings of confusion, anxiety, and other uncomfortable feelings such as fear and anxiety. The purpose of this study was to determine the effect of the application of Therapeutic Group Therapy and health education on the level of anxiety facing menarche in female students in RW 008, Delima Village, Tampan District, Pekanbaru. This type of Pre Experiment research with the One Group Pre Test Post Test design was carried out on 20 respondents, using the HARS scale questionnaire. This research will be carried out on students in RW 008, Delima Village, Tampan Pekanbaru District within an observation period of 4 months starting from September to December 2020. In sampling, this study uses the Non Probability Sampling technique with the type of Total Sampling where the sample selection method used is carried out based on certain goals or objectives determined by the researcher.